ANALISIS PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK ORIFLAME (Studi Kasus Pada Konsumen Oriflame Cabang Semarang ) - Maya Rina, 14.05.51.0100; Liana, Lie (Students' Journal of Economic and Management, 2018)
This research analyzes the influence of price, brand image and product quality on purchasing decision on Oriflame product (case study on Semarang branch of Oriflame consumer). Sampling technique in this study amounted to 100 respondents as a sample with data collection methods using questionnaires by distributing a list of questions to respondents to obtain information. The purpose of this study was formulated to determine the effect of price, brand image and product quality on purchasing decisions on Oriflame products. The collected data were analyzed using factor analysis to test the validity of question items, cronbach alpha formula to test the reliability of each independent variable tested by regression analysis. The results of his research are: Price has a positive and significant influence on the decision of purchasing Oriflame product. Brand image has no effect on the decision of purchasing Oriflame product. And Product quality has a positive and significant influence on the decision of purchasing Oriflame product.Keywords: price, brand image, product quality and purchase decision.